2005
DOI: 10.1037/0278-7393.31.6.1171
|View full text |Cite
|
Sign up to set email alerts
|

Specific-Token Effects in Screening Tasks: Possible Implications for Aviation Security.

Abstract: Screeners at airport security checkpoints perform an important categorization task in which they search for threat items in complex x-ray images. But little is known about how the processes of categorization stand up to visual complexity. The authors filled this research gap with screening tasks in which participants searched for members of target categories in visual displays. The authors found that when targets were sampled with replacement and repetition, participant screeners relied on recognizing familiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
20
2
Order By: Relevance
“…That is, all trials with a hammer target used the same hammer. There is evidence that observers learn specific targets and that this learning does not generalize well to other members of the same category (J. D. Smith, Redford, Washburn, & Taglialatela, 2005). Second, more critically, the three different targets were all from the "tools" category.…”
Section: Resultsmentioning
confidence: 99%
“…That is, all trials with a hammer target used the same hammer. There is evidence that observers learn specific targets and that this learning does not generalize well to other members of the same category (J. D. Smith, Redford, Washburn, & Taglialatela, 2005). Second, more critically, the three different targets were all from the "tools" category.…”
Section: Resultsmentioning
confidence: 99%
“…Research has demonstrated support for the specificity of training in similar airport luggage screening tasks (Smith, Redford, Washburn, & Taglialatela, 2005). Specifically, researchers found that participants relied on the recognition of familiar targets and had great difficulty using category-general knowledge (Smith, Redford, Gent, & Washburn, 2005;Smith, Redford, Washburn, & Taglialatela, 2005). In those studies, performance improved when the transfer images were the same as the ones used during training.…”
Section: U N C O R R E C T E D P Rmentioning
confidence: 97%
“…So far, the visual search and categorisation literature are rarely brought together (cf. Smith et al, 2005;Wolfe et al, 2007) because categorisation often requires identifying targets presented in isolation, whereas visual search requires discriminating targets from simultaneously presented distractors. Presumably, if training variability improved the visual differentiation of targets within cluttered bags, a possibility is that the benefit of training variability would disappear in the absence of cluttered images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations